A Study on the p-Adic Integral Representation on ℤp Associated with Bernstein and Bernoulli Polynomials. (19th September 2010) - Jang, Lee-Chae; Kim, Won-Joo; Simsek, Yilmaz
Abstract : We consider the Bernstein polynomials onℤ p and investigate some interesting properties of Bernstein polynomials related to Stirling numbers and Bernoulli numbers.